Phage-derived Hol49_Lys19/sodium alginate/chitosan composite green coating: Preparation, performance and preservation effect on refrigerated salmon - Shuxuan Li; Jing Li; Ming Zhang; Rundong Wang; Xiaoni Wang; Chunyan Li; Defu Zhang (Food Microbiology, 2027)

Numerical simulation on giant reed co-firing performance of circulating fluidized bed in thermal power plant to reduce carbon emission - Jiamiao Liu; Pengbo Zhao; Chenglong Yang; Qingwei Wang; Liujun Chang; Shi'en Liu; Chang'an Wang; Defu Che (Biomass and Bioenergy, 2026)

Novel contrastive representation learning of epileptic electroencephalogram for seizure detection - Jie Wang; Yingchao Wang; Qilin Tang; Xianlei Zeng; Defu Zhai; Han Xiao; Weiwei Nie; Qi Yuan (Cognitive Neurodynamics, 2026)

The influence of environmental factors and inducible enzyme fermentation broth on the lethality of Beauveria bassiana to Xylotrechus rusticus larvae - Yanchen Wang; Defu Chi (Journal of Invertebrate Pathology, 2026)

Coupled simulation of the combustion and hydrodynamics for predicting water-cooled wall temperature of a supercritical boiler during load variations - Chao Wang; Kairui Liu; Zhiyang Ma; Bin Liu; Rongze Gao; Limin Wang; Defu Che (Fuel, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Elevated hydrostatic pressure promotes organic carbon mineralization in reservoir sediments - Yan Zhang; Shangbin Xiao; Defu Liu; Wenjun Yang; Huiqun Cao; Jia Liu; Chenghao Wang; Li Zhu; Shijian Li; Shiping Lai; Xinghui Xia (Water Research, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Enhanced coarse-grained strategy for mixing process in high-solid content system - Yufan Bu; Xiangru Chen; Xiaofeng Wang; Liming Wang; Defu Che; Yulei Niu; Hai Nan (Chemical Engineering Journal, 2026)

Evaluation of Rice Yield Attributes, Loach Muscle Quality, and Soil Biochemical Composition Under Rice–Loach Coculture System - Chuanqi Yu; Wenlu Zhu; Wenjun Wang; Wenqiang Xu; Yu Liu; Xingtian Cai; Yanfa Xu; Defu Yang; Zhuqing Yang; Zirui Wang; Qiubai Zhou; Haohua He (Fishes, 2026)
This study aimed to evaluate rice yield attributes, loach Paramisgurnus dabryanus muscle quality, and soil biochemical composition under rice monoculture (RM), rice–loach coculture (RLC), and loach monoculture (LM). This trial was conducted for 90 days, and then rice, fish muscle and soil were obtained for analyses. The results showed that there were no significant differences in rice yield attributes between the rice–loach coculture (RLC) and rice monoculture (RM) groups. However, rice–loach coculture (RLC) improved muscle quality-related parameters, including increased hardness and springiness of loach muscle. Meanwhile, muscle metabolomic analysis showed that all the differentially expressed metabolites (DEMs) in the significantly enriched pathways of lysine degradation and lysine biosynthesis were up-regulated in the rice–loach coculture (RLC) group compared with the loach monoculture (LM) group. Furthermore, the rice–loach coculture (RLC) improved soil physicochemical properties, including an increase in microbial biomass nitrogen (MBN) content and activities of soil N-acquiring enzymes (NAG and LAP). Moreover, soil microbiome analysis showed that the abundance of Candidatus Koribacter versatilis, Acidobacteria bacterium WX27 and Pseudolabrys taiwanensis was significantly increased in the rice monoculture (RM) and rice–loach coculture (RLC) groups compared with the loach monoculture (LM) group. Pairwise Spearman’s correlation analysis of the top 30 soil microbial species and soil physicochemical properties indicated that Terrimonas sp. H1YJ31 showed a highly significant positive correlation with the soil N-acquiring enzymes (N-acetylglucosaminidase, NAG; leucine aminopeptidase, LAP) and a soil C-acquiring enzyme (exo-β-1,4-glucanase C1), whereas Gaiella occulta, Methyloceanibacter marginalis and Anaerohalosphaera lusitana had a highly significant negative correlation with S-NAG, S-LAP and S-C1. In short, the improved fish muscle quality and soil biochemical composition were ascribed to the increased hardness and springiness of loach muscle and the abundance of soil Terrimonas sp. H1YJ31.

Numerical Simulation on product generation and NO emission characteristics of iron Powder-Air combustion in a cyclone burner - Mengjie Wu; Yongbo Du; Chang’an Wang; Yujie Hou; Xinyue Gao; Junyan Gu; Wengang Bai; Defu Che (Fuel, 2026)

Soil texture regulates soil C mineralization by C substrates and microbial characteristics under vegetation restoration - Lingbo Dong; Weifang Hu; Defu Wang; Hailong Zhang; Jianzhao Wu; Jiwei Li; Rula Sa; Zhouping Shangguan; Lei Deng (Plant and Soil, 2026)

Influence of Fracture Geometry Parameters on the Mechanical Properties and Spatiotemporal Crack Evolution in Granite: Insights from Integrated AE and DIC Monitoring - Xiangyu Wang; Lei Zhang; Defu Zhu; Chunwang Zhang; Ze Wang; Zhenting Lv; Chengke Yang; Yu Zhang (Rock Mechanics and Rock Engineering, 2026)

LSSCM-MobileTeaNet: A UAV-based lightweight spatial–spectral convolution model for large-scale estimation of chlorophyll and nitrogen content in tea plantations - Guoquan Pei; Defu Liu; Hongyuan Shi; Zhengzhao Pi; Xueying Qian; Bing Zhou; Baijuan Wang; Wendou Wu (Computers and Electronics in Agriculture, 2026)

Gp8 mediates adsorption of bacteriophage vB_VpP_jzsmvpa to the host Vibrio parahaemolyticus - Shuxuan Li; Xiaoni Wang; Jing Li; Ming Zhang; Ke Liu; Xuepeng Li; Jianrong Li; Chunyan Li; Defu Zhang (Antonie van Leeuwenhoek, 2026)

Effects of Acute Heat Stress and Hypo-Salinity Exposure on Sea Cucumber Apostichopus japonicus by Widely Targeted Metabolomics Analysis - Qi Wang; Defu Gao; Bin Zhao; Wei Hu (Journal of Marine Science and Engineering, 2026)
Temperature and salinity are key environmental factors for sea cucumber (Apostichopus japonicus) aquaculture. To better understand the molecular regulation mechanisms of A. japonicus under extreme environmental conditions, we collected metabolomic data from a control group (C: 16 °C, 30 salinity), a heat-stress group (HT: 30 °C, 30 salinity), a hypo-salinity group (LS: 16 °C, 20 salinity), and a heat plus hypo-salinity group (HL: 30 °C, 20 salinity). Liquid chromatography–mass spectrometry-based metabolomics was used to measure the changes in endogenous metabolites in the body wall of A. japonicus and detect differential metabolites and associated metabolic pathways. The results of metabolomic profiling identified a total of 349 secondary metabolites, enriched mainly in unsaturated fatty acid metabolism, cAMP signaling pathway, pantothenic acid and coenzyme A biosynthesis, as well as vitamin metabolism. Compared to the control group, levels of amino acids and lipids were enhanced during adaptation to high-temperature stress (HT and HL groups). Levels of pantothenic acid content increased in the LS group compared with its content in the control group, which suggests that stress promoted the TCA cycle in the body of A. japonicus, providing energy for movement. A. japonicus may adjust energy metabolism by altering pathways or adapt to environmental changes by regulating the activities of certain enzymes to maintain life activities and metabolic homeostasis. In response to these stresses, A. japonicus metabolism increased to bolster its antioxidant capacity and maintain cellular homeostasis and organismal stability. These results clarified the complex physiological processes involved in the response to stress and the maintenance of metabolism of the A. japonicus. This study provides novel insights into the metabolic regulation mechanisms that enable A. japonicus to cope with heat and hypo-salinity stresses.

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Benchmarking and lightweight correction of daily near-surface air temperature products over the Qinghai-Tibetan Plateau - Nan Zhou; Yao Xiao; Lin Zhao; Guojie Hu; Lingxiao Wang; Chong Wang; Ren Li; Guangyue Liu; Defu Zou; Xiangfei Li (Atmospheric Research, 2026)

Acid-triggered degradation of a silicon-based nanopesticide activates SA-dependent conifer defense against Dioryctria sylvestrella - Zheng Wang; Antong Ma; Jiaxing Fang; Xiaoqi Xu; Wei Gan; Jiayue Liu; Fu Liu; Sufang Zhang; Defu Chi; Dafeng Chen; Yapei Wang; Xiangbo Kong (Pesticide Biochemistry and Physiology, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

Kinetic insights into the effects of coal quality and operating parameters on the NO and N2O formation behaviors in fluidized bed coal/ammonia co-combustion - Liangxu Dai; Ke Liu; Chang’an Wang; Yujie Hou; Tianlin Yuan; Zixiu Jia; Qiang Lyu; Defu Che (Fuel, 2026)

Experimental study on in-situ pyrolysis of tar-rich coal under CO2 heating: tar-gas products extraction and microstructural evolution - Meijing Chen; Liujun Chang; Chang’an Wang; Tianlin Yuan; Mengjie Wu; Yujie Hou; Defu Che (Fuel, 2026)

Evaluation of stability and cooling engineering effectiveness of the Qinghai-Tibet transportation routes: A first comprehensive assessment using space geodetic observations - Lingxiao Wang; Lin Zhao; Shibo Liu; Huayun Zhou; Guojie Hu; Defu Zou; Erji Du; Guangyue Liu; Yao Xiao; Yueli Chen; Jianting Zhao; Wei Chen; et al. (Engineering Geology, 2026)

Thermodynamic and economic analysis of aluminum-water reaction systems for power generation and energy storage - Xinyue Gao; Yongbo Du; Chang'an Wang; Yujie Hou; Mengjie Wu; Junyan Gu; Wengang Bai; Defu Che (Journal of Cleaner Production, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Mito-boosting nanovesicle hydrogel dressing rescues hepatocyte bioenergetic insufficiency and promotes post-hepatectomy regeneration - Yixiao Pan; Le Ding; Tangansu Zhang; Changjie Yang; Huimin Wu; Xiandong Zeng; Yingqiang Liang; Defu Kong; Shihang Yu; Yiwen Chen; Siyuan Pan; Hongye Wang; et al. (Chemical Engineering Journal, 2026)

Retraction notice to “Targeted delivery of honokiol by zein/hyaluronic acid core-shell nanoparticles to suppress breast cancer growth and metastasis” [Carbohydr. Polym. 240 (2020) 116325 - Qi Zhang; Jing Wang; Dan Liu; Wenquan Zhu; Shuang Guan; Li Fan; Defu Cai (Carbohydrate Polymers, 2026)

Spatial distribution of vegetation type in the Genhe River Basin based on multi-source data - Zhinan Zhou; Chong Wang; Lin Zhao; Defu Zou; Guangyue Liu; Shibo Liu; Lingxiao Wang; Guojie Hu; Zanpin Xing; Erji Du; Yao Xiao; Xueling Jiao (International Journal of Remote Sensing, 2025)

Control of backfill ratio in a short-wall green-intelligent mining working face to prevent pollution from coal-based solid waste: experimental and design studies on the relationship between two-dimensional images and volume of gangue - Yun Zhang; Yixuan Yang; Xingping Lai; Shenggen Cao; Yongzi Liu; Mingbo Chi; Defu Zhu; Baiyi Li; Di Wang; Jifeng Li (Journal of Cleaner Production, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Corrigendum to “Hyaluronic acid-modified liposomal honokiol nanocarrier: Enhance anti-metastasis and antitumor efficacy against breast cancer” [Carbohydr. Polym. 235 (2020) 115981] - Jing Wang; Dan Liu; Shuang Guan; Wenquan Zhu; Li Fan; Qi Zhang; Defu Cai (Carbohydrate Polymers, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Simulation study on mineral transformation behaviors and ash fusion characteristics during high-alkali coal combustion under deep peaking conditions - Jiamiao Liu; Guowei Ma; Yongbo Du; Chang’an Wang; Yonggang Zhao; Wanzhu Wu; Longping Shi; Lin Zhao; Defu Che (Fuel, 2025)

Research and Application of the Calculation Method for Vertical Stress of Interlayer Rock in Coal Mining Under Pillar Goaf - Qian Wang; Yujiang Zhang; Guorui Feng; Defu Zhu; Fudong Ma; Wushuai Hao; Shule Li; Shuai Zhang (Rock Mechanics and Rock Engineering, 2025)

Preliminary analysis of a slow-moving high-locality landslide in the Zagunao River Basin, Sichuan Province, China - Shengsen Zhou; Weile Li; Huiyan Lu; Zhou Xu; Wenlong Yu; Shanmiao Xu; Pan Zhang; Chunhao Wei; Yusen Li; Defu Wang; Weiwei Zhan; Qiang Xu (Bulletin of Engineering Geology and the Environment, 2025)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

Nitrogen and phosphorus release from a dominant plant in the water-level fluctuation zone of the Three Gorges Reservoir - Ying Liu; Ziyan Lu; Genghua Wu; Defu Liu; Henglin Xiao; Hong Yang; Heyun Wang; Jinhong Feng (Aquatic Sciences, 2025)

Improving the moving-grid permafrost model to reveal ground deformation and hydrothermal effects caused by permafrost evolution in the source region of the Yangtze river on the Qinghai-Tibet plateau - Zhe Sun; Lin Zhao; Guojie Hu; Shibo Liu; Yongping Qiao; Erji Du; Defu Zou; Guangyue Liu; Lingxiao Wang; Jianting Zhao (Environmental Modelling & Software, 2025)

Preparation of carbon nanosheet from molten salts assisted pyrolysis of biomass towards to carbon-negative technology - Sunwen Xia; Chen Zhang; Rui Fang; Yong Wang; Defu Shi; Bin Li; Dong Wang; Kuihua Han; Haiping Yang (Fuel, 2025)

Promising eco-friendly agents targeting Pseudomonas fluorescens biofilms - Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li; Lu Wang; Xue Bai (Food Bioscience, 2025)

Corrigendum to “Inhibition of growth and metastasis of breast cancer by targeted delivery of 17-hydroxy-jolkinolide B via hyaluronic acid-coated liposomes” [Carbohydr. Polym. 257 (2021) 117572] - Dan Liu; Qi Zhang; Jing Wang; Shuang Guan; Defu Cai; Jicheng Liu (Carbohydrate Polymers, 2025)

The surface features and internal structure of an integrated open system pingo in the source area of the Yangtze River on the Qinghai-Tibet Plateau - Guangyue Liu; Yao Xiao; Guojie Hu; Tonghua Wu; Xiaodong Wu; Lingxiao Wang; Changwei Xie; Defu Zou; Erji Du; Yonghua Zhao; Yingying Lu; Lin Zhao (CATENA, 2025)

Study on NO formation and ash characteristics during co-combustion of semi-coke and biomass under O2/CO2 conditions - Jinping Zhang; Jingchun Shen; Junyi Fang; Lei Chen; Chang’an Wang; Defu Che (Fuel, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

Regional landslide identification using the slope unit containing deformation information - Xiaohu Lei; Xiuying Wang; Shaojie Zhang; Hongjuan Yang; Defu Wang; Fangqiang Wei (Natural Hazards, 2025)

Study on characterization of tri-phase products and microstructure evolution during in-situ pyrolysis of tar-rich coal at different temperatures - Meijing Chen; Yongbo Du; Chang’an Wang; Tianlin Yuan; Yujie Hou; Liujun Chang; Lei Deng; Defu Che (Fuel, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

Effects of residual carbon on slag flow characteristics of Zhundong high-alkali coal under oxy-fuel condition - Yuanmao Chen; Chang’an Wang; Maoyun Luo; Lin Zhao; Pengbo Zhao; Defu Che (Fuel, 2025)

(C6H10N2)ZnX4·H2O (X=Cl and Br): Excellent nonlinear optical properties and temperature induced photoluminescence for encryption - Chuanying Shen; Chenyi Zhang; Qiwei Xing; Defu Sun; Kui Wu; Bingbing Zhang; Jiyang Wang; Duanliang Wang (Chemical Engineering Journal, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

Experimental investigation on thermal conductivity of tar-rich coal under the simulated in-situ conditions - Xing Ning; Xiaole Huang; Xiangyu Xue; Chang’an Wang; Lei Deng; Defu Che (Fuel, 2025)

Simulation study on seasonal recovery of waste heat and water resources in flue gas and slurry after WFGD - Gaofeng Fan; Xinyue Gao; Chang’an Wang; Yujie Hou; Jinming Zhang; Jie Xu; Defu Che (Process Safety and Environmental Protection, 2025)

Experimental investigation on gas-liquid–solid tri-phase product distributions during the simulated in-situ pyrolysis of tar-rich coal - Meijing Chen; Chang’an Wang; Tianlin Yuan; Xing Ning; Xiaole Huang; Lei Deng; Defu Che (Fuel, 2025)

Experimental study on characteristics and mechanism of hydrogen production from aluminium–water reaction for carbon-free power generation - Xinyue Gao; Chang’an Wang; Yujie Hou; Lin Zhao; Wengang Bai; Defu Che (Fuel, 2025)

Bacterial community structure and metabolomic profiles of yak milk and cattle-yak milk during refrigeration in Gannan region: Analysis of interspecific differences in milk spoilage - Hongqiang Li; Hongbo Wang; Yaqin Gao; Xiangmin Zhao; Jing Liang; Longying Pei; Yali Yao; Defu Tang (Food Chemistry, 2025)

Process and mechanism analysis of typical permafrost area surface deformation at two sites along the Qinghai-Tibet highway based on long-term leveling observation - Shibo Liu; Lin Zhao; Lingxiao Wang; Defu Zou; Guojie Hu; Zhe Sun; Huayun Zhou; Yongping Qiao (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Experimental study and chemical equilibrium calculation on the mineral transformation of high-alkali coal under oxy-fuel condition - Lin Zhao; Chang’an Wang; Yingchao Nie; Yongxu Chen; Jinming Zhang; Maoyun Luo; Defu Che (Fuel, 2024)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Multisource remote sensing monitoring and analyzing for land subsidence and crop growth in a coal mining area under different rainfall conditions - Baodong Ma; Renfeng Gao; Defu Che; Zhongyin Xu; Duo Wang; Yanen Sun (Environmental Development, 2024)

Progress in phosphorylation of natural products - Xiaoran Mao; Jiaqi Chen; Yingrui Yao; Defu Liu; Haiying Wang; Yuzhou Chen (Molecular Biology Reports, 2024)

Microbial communities associated with the mature sporophytes and sporelings of the commercially cultivated seaweed Saccharina japonica in Southern China - Yingrui Zhuang; Mahasweta Saha; Yan Bai; Suhelen Egan; Yixiao Han; Qiying Qiu; Defu Chen; Gaoge Wang (Journal of Applied Phycology, 2024)

Chemical kinetics simulation on nitrogen migration characteristics during co-combustion of ammonia and coal under deeply fuel-air multistage conditions - Liangxu Dai; Chang’an Wang; Yujie Hou; Guowei Ma; Yongxu Chen; Abu Hurera; Lei Zhou; Defu Che (Fuel, 2024)

Natural grassland restoration exhibits enhanced carbon sequestration and soil improvement potential in northern sandy grasslands of China: An empirical study - Huang Luxi; Gao Yong; Wang Defu; Cui Xiaojing; Zhang Huimin; Yuan Jiamao; Gao Miaomiao (CATENA, 2024)

Methane dynamics altered by reservoir operations in a typical tributary of the Three Gorges Reservoir - Jia Liu; Fei Xue; Xiaojuan Guo; Zhengjian Yang; Manchun Kang; Min Chen; Daobin Ji; Defu Liu; Shangbin Xiao; Chenghao Wang (Water Research, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

OsIPK1 frameshift mutations disturb phosphorus homeostasis and impair starch synthesis during grain filling in rice - Lina Wang; Jing Cui; Ning Zhang; Xueqin Wang; Jingping Su; María Pilar Vallés; Shian Wu; Wei Yao; Xiwen Chen; Defu Chen (Plant Molecular Biology, 2024)

Effects of drought and moisture stress on the growth and ecophysiological traits of Schima superba seedlings - Kashif Hussain; Defu Wang; Asif Riaz; Emily Patience Bakpa; Guilin Wu; Suping Liu; Yanxia Nie; Hui Liu (Photosynthesis Research, 2024)

Simultaneous hydroxyapatite-based phosphorus recovery and partial denitrification-anammox-based nitrogen removal during sludge leachate treatment - Ben Dai; Yifeng Yang; Zuobin Wang; Jingzhou Zhou; Xiaodi Li; Yi Yang; Defu Gan; Junxia He; Xin Zhang; Siqing Xia (Journal of Water Process Engineering, 2024)

Preparation of amorphous coal-based activated coke via a two-step process of carbonization and steam activation - Xiaoling Jin; Hui Wang; Hong An; Xiaoming Huang; Wenyan Zhang; Lei Deng; Defu Che (Fuel, 2024)

Effects of dietary Allium mongolicum Regel powder supplementation on the growth performance, meat quality, antioxidant capacity and muscle fibre characteristics of fattening Angus calves under heat stress conditions - Wangjing Liu; Huixia Gao; Jianjian He; Aihuan Yu; Chenxu Sun; Yaodi Xie; Haibo Yao; He Wang; Yueyan Duan; Jinsheng Hu; Defu Tang; Tao Ran; et al. (Food Chemistry, 2024)

Biogenic palladium nanoparticles for wastewater treatment: Formation, applications, limitations, and future directions - Xiaodi Li; Lin Yang; Jingzhou Zhou; Ben Dai; Defu Gan; Yi Yang; Zhenyu Wang; Junxia He; Siqing Xia (Journal of Water Process Engineering, 2024)

Effects of SO2 and H2O on the ash deposition and NO emission during oxy-fuel combustion of high-alkali coal - Lin Zhao; Chang’an Wang; Tianlin Yuan; Liangxu Dai; Yingchao Nie; Guowei Ma; Lei Zhou; Maoyun Luo; Defu Che (Process Safety and Environmental Protection, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Electric-field-controlled energy barrier and reaction pathway ensure high sulfur product selectivity in Cu/γ-Al2O3 catalyst-assisted DBD plasma conversion of carbonyl sulfide - Yixing Ma; Peng Chen; Defu Li; Fei Wang; Langlang Wang; Kai Li; Ping Ning; Xueqian Wang; Kostya (Ken) Ostrikov (Journal of Environmental Chemical Engineering, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

Exploring the link between microbial community structure and flavour compounds of traditional fermented yak milk in Gannan region - Hongqiang Li; Xiaoling Yang; Defu Tang; Bin Xi; Weihong Li; Zhaohui Chen; Yongqing Bao; Renqing Dingkao; Yaqin Gao; Peng Wang; Hongbo Wang (Food Chemistry, 2024)

Quantitative Proteomics Reveals Manganese Alleviates Heat Stress of Broiler Myocardial Cells via Regulating Nucleic Acid Metabolism - Shizhen Qin; Rui Wang; Jinlu Li; Defu Tang; Zhaoguo Shi (Biological Trace Element Research, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Correction to: Protective Efect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2024)

Penaeid shrimp counteract high ammonia stress by generating and using functional peptides from hemocyanin, such as HMCs27 - Mingming Zhao; Zhihong Zheng; Chuanqi Wang; Defu Yao; Zhongyang Lin; Yongzhen Zhao; Xiuli Chen; Shengkang Li; Jude Juventus Aweya; Yueling Zhang (Science of The Total Environment, 2023)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Green synthesis of bimetallic Pd Ag alloy nanoparticles supported on polydopamine-functionalized kaolin for catalytic reduction of 4-nitrophenol and organic dyes - Defu Gan; Zhenyu Wang; Xiaodi Li; Jingzhou Zhou; Ben Dai; Lin Yang; Siqing Xia (Applied Clay Science, 2023)

Novel ship fuel consumption modelling approaches for speed and trim optimisation: Using engine data as auxiliary - Kangli Wang; Defu Zhang; Zhenyu Shen; Wei Zhu; Hongcai Ye; Dong Li (Ocean Engineering, 2023)

Experimental investigation on co-combustion characteristics of semi-coke and coal: Insight into synergy and blending method - Pengqian Wang; Chang’an Wang; Chaowei Wang; Yongbo Du; Defu Che (Process Safety and Environmental Protection, 2023)

Simulation study on fuel-nitrogen migration characteristics of oxy-fuel co-combustion of various ultra-low volatile coal-based solid fuels - Chaowei Wang; Chang’an Wang; Maoyun Luo; Liangxu Dai; Pengqian Wang; Defu Che (Process Safety and Environmental Protection, 2023)

Investigation on Co-combustion characteristics and NO emissions of coal and municipal sludge in a tangentially fired boiler - Chang'an Wang; Meijing Chen; Pengbo Zhao; Lei Zhou; Yujie Hou; Jinming Zhang; Qiang Lyu; Defu Che (Fuel, 2023)

Synthesis of NaA zeolite from foundry dust and its adsorption capacity of ammonia - Mengqing Wang; Defu Xu; Hui Ma; Bing Li; Alan Howard (Journal of Environmental Management, 2023)

Effect of composted pig manure, biochar, and their combination on antibiotic resistome dissipation in swine wastewater-treated soil - Likun Sun; Defu Tang; Xisheng Tai; Jiali Wang; Min Long; Tingting Xian; Haofan Jia; Renfei Wu; Yongqi Ma; Yunpeng Jiang (Environmental Pollution, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

The transcription factor CEBP homolog of Penaeus vannamei contributes to WSSV replication - Chuanqi Wang; Huimin Zhang; Jinghua Zhu; Haiping Liu; Yiqing Yang; Bingbing Sun; Tingchu Wu; Yueling Zhang; Defu Yao (Fish & Shellfish Immunology, 2023)

An opportunistic pathogenic Pseudomonas isolated from healthy brown alga Saccharina japonica - Qin Yang; Yingrui Zhuang; Mahasweta Saha; Qiying Qiu; Defu Chen; Lirong Chang; Luyang Xiao; Gaoge Wang (Aquaculture, 2023)

Nutrient released characteristics of struvite-biochar fertilizer produced from concentrated sludge supernatant by fluidized bed reactor - Yingxue Li; Defu Xu; Haizhi Lin; Wenhua Wang; Hong Yang (Journal of Environmental Management, 2023)

Numerical simulation on co-firing ultra-low volatile carbon-based fuels with bituminous coal under oxy-fuel condition - Chang'an Wang; Yujie Hou; Qinqin Feng; Chaowei Wang; Xinyue Gao; Defu Che (Fuel, 2023)

Hydrogenation of N-ethylcarbazole with Hydrogen-Methane mixtures for hydrogen storage - Hu Liu; Jingwen Xue; Pengfei Yu; Yankang Zhang; Jinhua Wang; Defu Che (Fuel, 2023)

DRAXIN as a Novel Diagnostic Marker to Predict the Poor Prognosis of Glioma Patients - Yulong Jia; Zhendong Liu; Xingbo Cheng; Runze Liu; Pengxu Li; Defu Kong; Wenjia Liang; Binfeng Liu; Hongbo Wang; Xingyao Bu; Yanzheng Gao (Journal of Molecular Neuroscience, 2022)
An increasing number of evidences have shown that the carcinogenic effect of DRAXIN plays an important role in the malignant process of tumors, but the mechanism of its involvement in glioma has not yet been revealed. The main aim of this study is to explore the relationship between DRAXIN and the prognosis and pathogenesis of glioma through a large quality of data analysis. Firstly, thousands of tissue samples with clinical information were collected based on various public databases. Then, a series of bioinformatics analyses were performed to mine data from information of glioma samples extracted from several reputable databases to reveal the key role of DRAXIN in glioma development and progression, with the confirmation of basic experiments. Our results showed that high expression of the oncogene DRAXIN in tumor tissue and cells could be used as an independent risk factor for poor prognosis in glioma patients and was strongly associated with clinical risk features. The reverse transcription-quantitative PCR technique was then utilized to validate the DRAXIN expression results we obtained. In addition, co-expression analysis identified, respectively, top 10 genes that were closely associated with DRAXIN positively or negatively. Finally, in vitro experiments demonstrated that knockdown of DRAXIN significantly inhibited proliferation and invasion of glioma cell. To sum up, this is the first report of DRAXIN being highly expressed in gliomas and leading to poor prognosis of glioma patients. DRAXIN may not only benefit to explore the pathogenesis of gliomas, but also serve as a novel biological target for the treatment of glioma.

Protective Effect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2022)

Receptor-like kinase HAESA-like 1 positively regulates seed longevity in Arabidopsis - Defu Chen; Hongye Guo; Shuai Chen; Qianying Yue; Pei Wang; Xiwen Chen (Planta, 2022)

Metabolic reprogramming in crustaceans: A vital immune and environmental response strategy - Zhongyan Wang; Yueling Zhang; Defu Yao; Yongzhen Zhao; Ngoc Tuan Tran; Shengkang Li; Hongyu Ma; Jude Juventus Aweya (Reviews in Aquaculture, 2022)
Most host organisms undergo metabolic changes in response to pathogens, environmental cues or simply to boost their immunity. Metabolic modulation has therefore been exploited by both host and pathogens to outwit the other during host–pathogen interactions. Recent studies have revealed that a growing number of metabolites and metabolic processes in crustaceans are crucial in host–pathogen interactions. Here, we reviewed recent work on metabolic changes during immune response of crustaceans and the metabolic reprogramming that takes place in the host induced by pathogens, environmental cues or as a host strategy to withstand these changes or clear the pathogen. In aquaculture crustaceans, limited studies exist on this subject; hence, we will also highlight themes for possible future research on metabolite reprogramming and how this strategy can be leveraged to improve sustainable aquaculture and enhance crustaceans’ response to pathogens and environmental changes.

Manganese Mitigates Heat Stress–Induced Apoptosis by Alleviating Endoplasmic Reticulum Stress and Activating the NRF2/SOD2 Pathway in Primary Chick Embryonic Myocardial Cells - Shizhen Qin; Rui Wang; Defu Tang; Shijiao Qin; Yanli Guo; Zhaoguo Shi (Biological Trace Element Research, 2022)

Adaptability of organic matter and solid content to Fe2+/persulfate and skeleton builder conditioner for waste activated sludge dewatering - Xiaoran Li; Yafei Shi; Xi Zhou; Lu Wang; Huiqin Zhang; Kewu Pi; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2022)

Isolation and identification of a pathogenic bacterium, Exiguobacterium oxidotolerans XP-2, from the abnormal diseased mature sporophytes of a commercially cultivated brown seaweed Saccharina japonica - Rafiq Ahmad; Yao Chen; Yingrui Zhuang; Qiying Qiu; Defu Chen; Mahasweta Saha; Hongyan Wu; Gaoge Wang (Journal of Applied Phycology, 2021)

Responses of nitrogen transformation and dissolved oxygen in constructed wetland to biochar and earthworm amendment - Lei Zhou; Jiajun Wang; Defu Xu; Yingxue Li; Bin Yao; Alan Howard (Environmental Science and Pollution Research, 2020)

A new closterovirus in Alcea rosea identified by small RNA deep sequencing - Defu Wang; Liyan Cui; Peixia Yu; Yonghong Qi; Baoxia Wang; Yanbing Niu (Journal of Plant Pathology, 2020)

Numerical Analysis of Sandwich Composite Deep Submarine Pressure Hull Considering Failure Criteria - Mahmoud Helal; Huinan Huang; Defu Wang; Elsayed Fathallah (Journal of Marine Science and Engineering, 2019)
The pressure hull is the primary element of submarine, which withstands diving pressure and provides essential capacity for electronic systems and buoyancy. This study presents a numerical analysis and design optimization of sandwich composite deep submarine pressure hull using finite element modeling technique. This study aims to minimize buoyancy factor and maximize deck area and buckling strength factors. The collapse depth is taken as a base in the pressure hull design. The pressure hull has been analyzed using two composite materials, T700/Epoxy and B(4)5505/Epoxy, to form the upper and lower faces of the sandwich composite deep submarine pressure hull. The laminated control surface is optimized for the first ply failure index (FI) considering both Tsai–Wu and maximum stress failure criteria. The results obtained emphasize an important fact that the presence of core layer in sandwich composite pressure hull is not always more efficient. The use of sandwich in the design of composite deep submarine pressure hull at extreme depths is not a safe option. Additionally, the core thickness plays a minor role in the design of composite deep submarine pressure hull. The outcome of an optimization at extreme depths illustrates that the upper and lower faces become thicker and the core thickness becomes thinner. However, at shallow-to-moderate depths, it is recommended to use sandwich composite with a thick core to resist the shell buckling of composite submarine pressure hull.

In-depth proteomic profiling of the Singapore grouper iridovirus virion - Defu Yao; Yingfu Liu; Xiuli Chen; Teck Kwang Lim; Lili Wang; Jude Juventus Aweya; Yueling Zhang; Qingsong Lin (Archives of Virology, 2019)

Filtered maximum likelihood expectation maximization based global reconstruction for bioluminescence tomography - Defu Yang; Lin Wang; Dongmei Chen; Chenggang Yan; Xiaowei He; Jimin Liang; Xueli Chen (Medical & Biological Engineering & Computing, 2018)

Deep sequencing analysis of a strain of pecan mosaic-associated virus infecting Atractylodes macrocephala Koidz - Yanbing Niu; Xiaojing Pang; Defu Wang; Shang Guo; Yong Liu (Journal of Plant Pathology, 2018)

Molecular detection of watermelon mosaic virus associated with a serious mosaic disease on Cucurbita pepo L. in Shanxi, China - Yanbing Niu; Xiaojing Pang; Yuanyuan Cheng; Defu Wang; Shang Guo; Yong Liu (VirusDisease, 2017)

Impacts of low-molecular-weight organic acids on aquatic behavior of graphene nanoplatelets and their induced algal toxicity and antioxidant capacity - Zhuang Wang; Yucheng Gao; Se Wang; Hao Fang; Defu Xu; Fan Zhang (Environmental Science and Pollution Research, 2016)

Behavioral and physiological responses of forest musk deer (Moschus berezovskii) to experimental fawn manipulation - Wenxia Wang; Lan He; Shuqiang Liu; Torsten Wronski; Defu Hu (acta ethologica, 2016)

Air quality improvement during 2010 Asian games on blood coagulability in COPD patients - Zili Zhang; Jian Wang; Meihua Guo; Mingmei Xiong; Qipeng Zhou; Defu Li; Jiaze Shu; Wenju Lu; Dejun Sun (Environmental Science and Pollution Research, 2016)

The wheat homolog of putative nucleotide-binding site–leucine-rich repeat resistance gene TaRGA contributes to resistance against powdery mildew - Defu Wang; Xiaobing Wang; Yu Mei; Hansong Dong (Functional & Integrative Genomics, 2016)

Performance investigation of SP3 and diffusion approximation for three-dimensional whole-body optical imaging of small animals - Defu Yang; Xueli Chen; Xu Cao; Jing Wang; Jimin Liang; Jie Tian (Medical & Biological Engineering & Computing, 2015)

Identification and Characterization of Human MIBP1 Gene in Glioma Cell Differentiation - Lijun Sun; Xiwen Chen; Xingnan Jin; Qiang Huang; Weilan Wang; Dashi Zhi; Defu Chen (Journal of Molecular Neuroscience, 2014)

Transmembrane routes of cationic liposome-mediated gene delivery using human throat epidermis cancer cells - Shaohui Cui; Bing Wang; Yinan Zhao; Huiying Chen; Huiqin Ding; Defu Zhi; Shubiao Zhang (Biotechnology Letters, 2014)

Knockdown of ZNF403 inhibits cell proliferation and induces G2/M arrest by modulating cell-cycle mediators - Rui Guan; Xiao-Yan Wen; Jing Wu; Rongqi Duan; Huibi Cao; Simon Lam; Defu Hou; Youdong Wang; Jim Hu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2012)

Transgenic tobacco plants expressing atzA exhibit resistance and strong ability to degrade atrazine - Huizhuan Wang; Xiwen Chen; Xuguang Xing; Xiaohua Hao; Defu Chen (Plant Cell Reports, 2010)

Evaluation of Goldmann Applanation Tonometry Using a Nonlinear Finite Element Ocular Model - Ahmed Elsheikh; Defu Wang; Aachal Kotecha; Michael Brown; David Garway-Heath (Annals of Biomedical Engineering, 2006)